1993
DOI: 10.1007/bf00666351
|View full text |Cite
|
Sign up to set email alerts
|

DNA ploidy, S-phase, and steroid receptors in more than 127,000 breast cancer patients

Abstract: Several potential prognostic factors are available today for patients with breast cancer, and many more are being identified and studied. To evaluate the clinical utility of these factors, it will be necessary to measure them on a large number of patients, and then follow these patients so that multivariate survival analyses can be performed. The Oncology Research Network was established in 1986 by the University of Texas Health Science Center at San Antonio and Nichols Institute Reference Laboratories in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
64
0
4

Year Published

1998
1998
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(81 citation statements)
references
References 28 publications
13
64
0
4
Order By: Relevance
“…Deregulation of cell cycle checkpoints, development of genomic instability, and aneuploidy are hallmarks of breast cancer (Anbazhagan et al, 1991;Wenger et al, 1993;Gunther et al, 1997). Genomic instability represents a major problem in the management of breast cancer patients due to the generation of diverse tumor cell phenotypes, which in turn may facilitate the development of chemoresistance and tumor progression (Khong and Restifo, 2002;Pinto et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Deregulation of cell cycle checkpoints, development of genomic instability, and aneuploidy are hallmarks of breast cancer (Anbazhagan et al, 1991;Wenger et al, 1993;Gunther et al, 1997). Genomic instability represents a major problem in the management of breast cancer patients due to the generation of diverse tumor cell phenotypes, which in turn may facilitate the development of chemoresistance and tumor progression (Khong and Restifo, 2002;Pinto et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 127 000 breast tumors, about one-half were found to be diploid or near diploid, the others exhibiting various types of aneuploidy (Wenger et al 1993). In an analysis of 256 patients, 384 modal chromosome numbers were detected, ranging between 29 and 211; 74% of these modal numbers were between 41 and 50, 19% between 51 and 80.…”
Section: Aneuploidymentioning
confidence: 99%
“…These have repeatedly demonstrated that ERα-cancers have, on average, an increased proliferation rate compared to their ERα+ counterparts. [35][36][37] Increased proliferation rates are associated with a decreased time to relapse [38][39][40] and decreased overall survival. 41 Furthermore, the benefits of chemotherapy in terms of survival or response appear to be greatest for high growth rate tumors, 42,43 although results from some studies do not support this relationship.…”
Section: Introductionmentioning
confidence: 99%